2012
DOI: 10.1093/jpids/pis034
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infections at a Children's Cancer Hospital, 1983–2008

Abstract: Background. Little is known about the incidence and etiology of healthcare-associated infections in immunosuppressed children. Methods. Data collected prospectively between 1983 and 2008 were used to analyze changes in the rate, types of infection, and infecting organisms over time in patients treated at a children's cancer hospital. Neutropenia was evaluated as a risk factor. Results. Over the 26-year study period, 1986 healthcare-associated infections were identified during 1653 hospitalizations. The infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Our study has several strengths related to the institutional setting and study design. All patients were treated according to a single protocol at a single institution and were provided with high-quality supportive care [2,27,28]. We used prespecified standard definitions of febrile neutropenia, clinically or microbiologically documented infection (which includes nonbacterial infections), and BSI [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several strengths related to the institutional setting and study design. All patients were treated according to a single protocol at a single institution and were provided with high-quality supportive care [2,27,28]. We used prespecified standard definitions of febrile neutropenia, clinically or microbiologically documented infection (which includes nonbacterial infections), and BSI [15].…”
Section: Discussionmentioning
confidence: 99%
“…These were consistent with previously reported studies in Latin America and from a major pediatric cancer center in the USA. 6,19 While any type of HAI event can have serious consequences, the incidence of Clostridoides difficile infections (CDI) has been problematic since these events cause cancer treatment delays and prolonged length of stay. 20 During the study period, thirty-one CDI events were observed in total between the PICU and IMCU.…”
Section: Discussionmentioning
confidence: 99%
“…3 Central line-associated bloodstream infections (CLABSI), multidrug-resistant organisms (MDROs), gastrointestinal-related infections, and viral infections are the most commonly seen HAIs affecting pediatric hematology-oncology patients. [4][5][6] There is growing knowledge about the role of the healthcare environment as a reservoir of and vehicle for the transmission of various pathogens and how environmental cleaning and sterilization practices can help decrease the transmission of HAIs. [7][8][9] Pathogens can survive in the environment from several hours to two weeks for Norovirus, seven days up to five years for methicillin-resistant Staphylococcus aureus (MRSA), greater than five months for Clostridioides difficile and from five days to five years for vancomycin-resistant enterococci (VRE).…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infections are the most common health careassociated infections (HAI) in pediatric cancer patients with Gram-positive cocci, in particular S. aureus , being the most common agents. 49 In children with malignancy, S. aureus accounts for up to 9%–13% of neutropenic bloodstream infections and febrile neutropenia. 50 , 51 Moreover, S. aureus has been the most commonly reported cause of infectious death in some studies of pediatric febrile neutropenia.…”
Section: Children With Malignancymentioning
confidence: 99%